2015
DOI: 10.1016/j.myc.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

New collection, iconography and molecular evidence for Tylopilus neofelleus (Boletaceae, Boletoideae) from southwestern China and the taxonomic status of T. plumbeoviolaceoides and T. microsporus

Abstract: (AAM) is copyrighted and published by Elsevier. It is posted here by agreement between Elsevier and the University of Turin. Changes resulting from the publishing process-such as editing, corrections, structural formatting, and other quality control mechanisms-may not be reflected in this version of the text. The definitive version of the text was subsequently published in MYCOSCIENCE, 55 (4), 2015, 10.1016/j.myc.2014.12.001. You may download, copy and otherwise use the AAM for non-commercial purposes provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…During macrofungal surveys to different forested areas of Eastern Himalaya (Sikkim) and Western Himalaya, three interesting members of Tylopilus were collected separately. Detailed macro- and micromorphological studies followed by phylogenetic analyses based on nrLSU and nrITS sequences, confirm the novelty of two of them and are proposed here as T. himalayanus and T. pseudoballoui , whereas the third one appeared as conspecific to T. neofelleus (a species so far reported from Japan and China, Gelardi et al 2015) and is reported as a new record for Indian mycobiota.…”
Section: Introductionsupporting
confidence: 74%
See 4 more Smart Citations
“…During macrofungal surveys to different forested areas of Eastern Himalaya (Sikkim) and Western Himalaya, three interesting members of Tylopilus were collected separately. Detailed macro- and micromorphological studies followed by phylogenetic analyses based on nrLSU and nrITS sequences, confirm the novelty of two of them and are proposed here as T. himalayanus and T. pseudoballoui , whereas the third one appeared as conspecific to T. neofelleus (a species so far reported from Japan and China, Gelardi et al 2015) and is reported as a new record for Indian mycobiota.…”
Section: Introductionsupporting
confidence: 74%
“…Japan (Kawamura 1954; Hongo 1960; Imazeki et al 1970, 1988; Takahashi 1986; Gelardi et al 2015), China (Ying and Zang 1994; Li and Song 2000; Wang et al 2004; Fu et al 2006; Wu et al 2011; Gelardi et al 2015), Russia (Vasil’jeva 1978) and New Guinea (Hongo 1973). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations